The forms of the affects - Brinkema, Eugenie, 1980- (Duke University Press, 2014)
What is the relationship between a cinematic grid of color and that most visceral of negative affects, disgust? How might anxiety be a matter of an interrupted horizontal line, or grief a figure of blazing light? Offering a bold corrective to the emphasis on embodiment and experience in recent affect theory, Eugenie Brinkema develops a novel mode of criticism that locates the forms of particular affects within the specific details of cinematic and textual construction. Through close readings of works by Roland Barthes, Hollis Frampton, Sigmund Freud, Peter Greenaway, Michael Haneke, Alfred Hitchcock, Søren Kierkegaard, and David Lynch, Brinkema shows that deep attention to form, structure, and aesthetics enables a fundamental rethinking of the study of sensation. In the process, she delves into concepts as diverse as putrescence in French gastronomy, the role of the tear in philosophies of emotion, Nietzschean joy as a wild aesthetic of repetition, and the psychoanalytic theory of embarrassment. Above all, this provocative work is a call to harness the vitality of the affective turn for a renewed exploration of the possibilities of cinematic form